Field report PAC 671: Syam & Co Chartered Accountants / Nur Iffah Liyana Mohd Sohaimi - Mohd Sohaimi, Nur Iffah Liyana (Universiti Teknologi MARA, Terengganu, 2024)
Syam & Co provides accounting services, including bookkeeping, financial statement preparation, and management accounting. These services are tailored to help businesses maintain accurate financial records and make informed decisions. Other than that, the firm also offers tax services such as tax planning, compliance, and advisory. Their expertise ensures clients optimize their tax obligations and remain compliant with the latest tax laws and regulations. Syam & Co conducts thorough audits to assess the accuracy and fairness of financial statements which help clients identify areas for improvement and maintain stakeholder confidence. The corporate advisory services at Syam & Co include business consulting, mergers and acquisitions, and corporate restructuring. These services are designed to support clients in strategic planning and enhancing business performance.